Structure of African Swine Fever Virus and Associated Molecular Mechanisms Underlying Infection and Immunosuppression: A Review - Wang, Yue; Kang, Weifang; Yang, Wenping; Zhang, Jing; Li, Dan; Zheng, Haixue (Frontiers in Immunology, 2021)
African swine fever (ASF) is an acute, hemorrhagic, and deadly infectious disease. The mortality rate of the most acute and acute ASF infection is almost 100%. The World Organization for Animal Health (OIE) lists it as a legally reported animal disease and China lists it as classⅠanimal epidemic. Since the first diagnosed ASF case in China on August 3, 2018, it has caused huge economic losses to animal husbandry. ASF is caused by the African swine fever virus (ASFV), which is the only member of Asfarviridae family. ASFV is and the only insect-borne DNA virus belonging to the Nucleocytoplasmic Large DNA Viruses (NCLDV) family with an icosahedral structure and a capsule. Till date, there are still no effective vaccines or antiviral drugs for the prevention or treatment of ASF. The complex viral genome and its sophisticated ability to regulate the host immune response may be the reason for the difficulty in developing an effective vaccine. This review summarizes the recent findings on ASFV structure, the molecular mechanism of ASFV infection and immunosuppression, and ASFV-encoded proteins to provide comprehensive proteomic information for basic research on ASFV. In addition, it also analyzes the results of previous studies and speculations on the molecular mechanism of ASFV infection, which aids the study of the mechanism of clinical pathological phenomena, and provides a possible direction for an intensive study of ASFV infection mechanism. By summarizing the findings on molecular mechanism of ASFV- regulated host cell immune response, this review provides orientations and ideas for fundamental research on ASFV and provides a theoretical basis for the development of protective vaccines against ASFV.